Water Quality - New Perspectives 2024
DOI: 10.5772/intechopen.108349
|View full text |Cite
|
Sign up to set email alerts
|

Role of Activated Carbon in Water Treatment

Abstract: Heavy metals, such as lead, mercury, zinc, aluminum, arsenic, nickel, chromium, and cobalt, are the common pollutants present within the environment from various natural and Industrial sources. Synthetic dyes are commonly used for dyeing and printing in a variety of industries. The traditional methods for the removal of heavy metals and dyes from wastewater are chemical precipitation, ion exchange, adsorption, membrane processes, and evaporation which require high capital investment and running costs. Activate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Fortunately, several material classes exhibit remarkable resilience in these scenarios. Activated carbon, with its large surface area and diverse functional groups, excels in adsorbing organic pollutants across a wide pH range [ 41 ]. Modified clays like zeolites boast tunable pore sizes and surface charges, enabling targeted adsorption of specific contaminants even amidst fluctuating pH [ 42 , 43 ].…”
Section: Advances To Overcome Current Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, several material classes exhibit remarkable resilience in these scenarios. Activated carbon, with its large surface area and diverse functional groups, excels in adsorbing organic pollutants across a wide pH range [ 41 ]. Modified clays like zeolites boast tunable pore sizes and surface charges, enabling targeted adsorption of specific contaminants even amidst fluctuating pH [ 42 , 43 ].…”
Section: Advances To Overcome Current Limitationsmentioning
confidence: 99%
“…Its exceptional adsorption capabilities are attributed to its extensive surface area and porous structure. However, generating activated carbon can demand significant energy, and its effectiveness might decline over time, necessitating the need for regeneration or replacement [ 41 ]. Zeolites, another category of adsorbents, are effective in removing cations, such as heavy metals, from water.…”
Section: Comparative Evaluation Of Adsorption Techniquesmentioning
confidence: 99%
“…The activation process is accomplished by heating and steaming the coal and biomass, which creates a structure with minuscule holes and fissures in the precursor material that may catch and retain particles from gases or liquids traveling through it [1,3,10]. Due to its enormous microporous structure, activated carbon is frequently utilized in a variety of industrial treatments, including chemical treatment, protective suits, water and air filtration, and environmental remediation [3,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals and anions present in drinking water become a challenging public issue due to their causes in human health. Jaya Rajan and Indira Anish [13] pointed out that a removal efficiency of 150 mg/g was observed for cadmium removal using biomass-activated carbon. Aziz et al [23] found out that the activated carbon produced in his study was efficient at adsorbing contaminants from water, with removal efficiencies up to 100%.…”
Section: Introductionmentioning
confidence: 99%